Lexical and Contextual Meaning in the Off-Season Album By J. Cole - Muhamad Haykhal (Sean Institute, 2025)
This research analyzes the lexical and contextual meanings found in selected song lyrics from the album The Off-Season by J. Cole. The purpose of this study is to analyze how language is used by artists to convey deeper meanings, emotions, and social commentary through dictionary-based definitions (lexical meaning) and meanings derived from context (contextual meaning). This research uses a descriptive qualitative method, focusing on several songs that contain rich linguistic and cultural content. This research found 53 lyric lines that contain lexical and contextual meaning in the whole album The Off-Season by J. Cole. The results of the analysis show that J. Cole often uses figurative language, slang, metaphors, and culturally embedded expressions to deliver messages about identity, struggle, success, and social issues. The findings suggest that understanding lexical and contextual meanings is crucial to interpreting the depth and intent of J. Cole's lyrics. This research aims to contribute to the wider field of linguistics, particularly in the areas of semantics and discourse analysis in music and popular culture.